Determining the informational needs of family caregivers of people with intellectual disability who require palliative care: A qualitative study. Issue 4 (August 2021) - McKibben, Laurie; Brazil, Kevin; McLaughlin, Dorry; Hudson, Peter
Abstract: Objectives: People with intellectual disabilities are living longer, and many require palliative care. There is a lack of evidence regarding information needs which may exist for their family caregivers. This study aimed to determine the informational needs of family caregivers of people with intellectual disabilities who require palliative care. Methods: A qualitative, exploratory design was underpinned by the Transactional Model of Stress and Coping and the Transformative Paradigm. The study involved five Health and Social Care (HSC) Trusts and two Hospices in one region of the United Kingdom. Family caregivers ( n = 10) participated in individual interviews. HSC professionals' ( n = 28) perceptions of informational needs were explored within focus groups ( n = 6). Results: Family caregivers reported information needs chiefly concerning the disease, financial entitlements, and practical support which could change over the disease trajectory. Findings evidence the expertise of long-term family caregivers, prior to the end of life. Palliative care and intellectual disability teams acknowledged their role to work in partnership and facilitate access to information. Recommendations were mapped onto a co-designed logic model. Significance of results: New insights into the specific informational needs of this family caregiving population. A co-designed logic model presents these needs and how they may be addressed. Central co-ordinators have been advocated for these caregivers. This model could have international applicability for similar family carers, supporting people with other disabilities or cognitive impairment, and should be further explored.